Partisipasi Mahasiswa KKP Desa Nyurlembang Dalam Program Operasi Plastik Awet Muda Sebagai Upaya Menjaga Lingkungan - Nabila, Riska (LP3M Universitas Putra Bangsa, 2023)
The use of plastic has expanded in various aspects of daily life, including household appliances, automotive, electronics, medical equipment, and agriculture. However, the extensive use of plastic also brings about negative consequences in the form of increased plastic waste, which is challenging to decompose and can harm the environment while posing health risks. The